2019
DOI: 10.1182/bloodadvances.2019000576
|View full text |Cite
|
Sign up to set email alerts
|

Results of CoALL 07-03 study childhood ALL based on combined risk assessment by in vivo and in vitro pharmacosensitivity

Abstract: Key Points Report of the long-term outcome of children with acute lymphoblastic leukemia upon risk-adapted therapy accrued in trial CoALL 07-03. Lack of correlation between in vitro and in vivo drug response as well as a lower predictive value of in vitro drug testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…Greater prognostic heterogeneity of ETV6-RUNX1 (+) ALL patients may be the key factor for patients with high hyperdiploidy having significantly better EFS than those with ETV6-RUNX1 fusion in our study group. Overall, our results underscore the disparate outcome for the two canonical good prognosis genetic abnormalities of Pre-B ALL, and lower survival of our ETV6-RUNX1 (+) ALL patients (10-year EFS of 79.5±4.4%) compared to the excellent survival rates reported in past studies [ 2 , 8 , 9 ].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Greater prognostic heterogeneity of ETV6-RUNX1 (+) ALL patients may be the key factor for patients with high hyperdiploidy having significantly better EFS than those with ETV6-RUNX1 fusion in our study group. Overall, our results underscore the disparate outcome for the two canonical good prognosis genetic abnormalities of Pre-B ALL, and lower survival of our ETV6-RUNX1 (+) ALL patients (10-year EFS of 79.5±4.4%) compared to the excellent survival rates reported in past studies [ 2 , 8 , 9 ].…”
Section: Discussionsupporting
confidence: 58%
“…Although one past nationwide study showed a significantly higher relapse-free survival for girls compared with boys [ 15 ], recent studies have shown comparable outcome according to patient sex [ 2 , 9 , 10 ]. In our study, boys had lower 10-year EFS compared with girls, and patient sex proved to be a significant prognostic factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Schramm et al recently demonstrated a lack of correlation between in vitro and in vivo drug response, as well as a lower predictive value of in vitro drug testing, reflecting an intrinsic limitation of this methodology that prevents its use for treatment stratification in future trials. Here, a simple fast in vitro model was prospectively applied for response prediction and treatment stratification accordingly using a 2D monoculture of patient samples and the methyl-thiazoltetrazolium viability assay [6]. The most widely used preclinical in vivo models for hematological malignancies are human tumor xenografts in immunodeficient mice [7].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in childhood ALL treatment Результаты лечения острого лимфобластного лейкоза по современным протоколам терапии[10,26,[29][30][31][32][33] Treatment results of acute lymphoblastic leukemia according to modern therapy protocols[10,26,[29][30][31][32][33] …”
unclassified